ASESMEN KINERJA (PERFORMANCE ASSESSMENT) DALAM PEMBELAJARAN MATEMATIKA - Suci Yuniati (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2011)
The system for assessment in mathematics is dominated by a single method of assessment that is paper and pencil test that only measures students' memories of factual information and procedures of the algorithm alone. Its domination can be seen from the questions the National Examination (UN) and the National Selection Entry State University (SNMPTN). The use of the objective tests in these matters encourages teachers to give similar exercises to students as they have to answer the questions of this form. Even the students are taught